2020
DOI: 10.1111/jfpp.14766
|View full text |Cite
|
Sign up to set email alerts
|

Top‐spray fluidization coating of paddy rice with zinc oxide nanoparticles to reduce infection fromAspergillussp

Abstract: Paddy rice varieties harvested in the rainy season are generally at risk of fungal contamination. This includes the local paddy rice variety, Sang Yod, that is harvested annually and requires a specific climate and agricultural geography for growth (Ministry of Commerce, 2006). After maturity, most farmers in Thailand, who not have a large godown and equipment for rice production, will sell the paddy rice to the nearest rice community enterprise, cooperative, or factory immediately after harvesting. The paddy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To concentrate only on the change of the crystalline form of the n‐ZnO that was coated on the surface of the treated sample under different conditions, we began by testing at a diffraction angle of 30°. Kongtragoul and Junka (2020) reported that diluting n‐ZnO powder to a solution using distilled water can decrease the intensity of all peaks and only peaks with a high intensity can be detected. The change in the intensity also depends on the quality and quantity of the coating material.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To concentrate only on the change of the crystalline form of the n‐ZnO that was coated on the surface of the treated sample under different conditions, we began by testing at a diffraction angle of 30°. Kongtragoul and Junka (2020) reported that diluting n‐ZnO powder to a solution using distilled water can decrease the intensity of all peaks and only peaks with a high intensity can be detected. The change in the intensity also depends on the quality and quantity of the coating material.…”
Section: Resultsmentioning
confidence: 99%
“…As suggested by the College of Nanotechnology at King Mongkut's Institute of Technology Ladkrabang, Bangkok, Thailand, n‐ZnO powder was mixed with distilled water at the lowest level of density of 400 ppm. The solution was injected at a flow rate of 0.6 ml/s and a pressure at 3.5 bar through a nozzle installed 35 cm above the distributor (Kongtragoul & Junka, 2020). Before the procedure started, air was let in through the air inlet tube and was warmed by the heater to enable the system to be in a steady state in accordance with the experimental hot air temperature, which was in the range of 70–130°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations